Effect of Enhanced Recovery after Surgery (ERAS) protocol on maternal outcomes following emergency caesarean delivery: A randomized controlled trial - Rajlaxmi Mundhra; Dipesh Kumar Gupta; Anupama Bahadur; Ajit Kumar; Rakesh Kumar (Elsevier, 2024)
Background: With ever increasing rates of emergency caesarean deliveries (CD),incorporating the ERAS protocol might provide a perfect window of opportunity to increase maternal comfort during the postsurgical period, but also improve outcomes and facilitate optimal return of physiological function. Objective: To determine whether an ERAS pathway at emergency caesarean birth would permit a reduction in postoperative length of stay and improve postoperative patient satisfaction. Material & methods: Patients undergoing emergent caesarean delivery at ≥ 34 weeks of gestation were randomized to ERAS or conventional care. The primary outcome was to compare postoperative length of hospital stay. Secondary outcome variables included first oral intake, passage of flatus/defecation, first ambulation, first urination after catheter removal and postoperative pain scores in both groups. Results: We randomized 142 women (71 each in ERAS versus Conventional arm) undergoing emergency cesarean delivery. Incorporation of ERAS protocol resulted in shorter length of hospital stay (73.92 ± 8.96 in conventional arm vs 53.87 ± 15.02 in ERAS arm; p value <.0001). Significant difference was seen in visual analogue scoring during initial ambulation and rest on day 0 and day 1 between ERAS and conventional arms with mean scores being lower in ERAS arm compared to Conventional arm (p value <.05). In terms of quality of life, ERAS arm had better quality of life compared to conventional arm Conclusion: Incorporation of ERAS protocol in emergency caesarean definitely improves patient outcome in terms of early resumption of activities with better quality of life.